Pembiasaan Kegiatan Keagamaan dan Keterampilan untuk Peningkatan Kompetensi Lulusan di SMA Islam - Masyharudin, Ali (TA'LIMUNA: Jurnal Pendidikan Islam, 2022)
Abstract: Improving the quality of graduate competencies, the learning process is not only in the form of material but can be presented in a program of habituation of religious activities (practice) directly and through skill activity programs in the form of practice according to talents and interests. student interests. This study aims to find out (1) analyze the scope of improving the quality of graduate competence through religious activities and skills (2) analyze the supporting and inhibiting factors for improving the quality of graduate competence through religious activities (3) analyzing solutions to barriers to improving the quality of graduate competence through skills activities. This study uses a qualitative approach. The results of this study are: (1) integrated with other subjects, the Minister of Education and Culture, curriculum and school characteristics, (2) Supporting and inhibiting factors from most of the internal institutions and students, (3) the solution to these obstacles is the management of synergistic activities as well as empowerment. students maximally and collaboratively. The implication is that by collaborating the three models, the quality of graduates has human characters who are religious, have noble character and have an entrepreneurial spirit who are able to face the challenges of the 5.0 Qur'an-based technology era. an and Al-Hadith..Keywords: Graduate competence, habituation, religion activities, skills   Abstrak: Peningkatan kualitas kompetensi lulusan, proses pembelajaran tidak hanya dalam bentuk materi tetapi dapat disajikan dalam program pembiasaan kegiatan keagamaan (praktik) secara langsung dan melalui program kegiatan keterampilan berupa praktik sesuai bakat dan minat. kepentingan siswa. Penelitian ini bertujuan untuk mengetahui (1) menganalisis ruang lingkup peningkatan kualitas kompetensi lulusan melalui kegiatan keagamaan dan keterampilan (2) menganalisis faktor pendukung dan penghambat peningkatan mutu kompetensi lulusan melalui kegiatan keagamaan (3) menganalisis solusi dari hambatan peningkatan mutu kompetensi lulusan melalui kegiatan keterampilan pada. Penelitian ini menggunakan pendekatan kualitatif. Hasil penelitian ini adalah: (1) terintegrasi dengan mata pelajaran lain, mendikbud, kurikulum dan karakteristik sekolah, (2) Faktor pendukung dan penghambat dari kebanyakan dari internal lembaga dan siswa, (3) solusi dari hambatan itu yaitu pengelolaan kegiatan yang sinergis sekaligus pemberdayaan siswa secara maksimal dan kolaboratif. Implikasinya yaitu mengkolaborasikan ketiga model tersebut, kualitas lulusan memiliki karakter manusia yang agamis, berakhlak mulia dan memiliki jiwa wirausaha yang mampu menghadapi tantangan era teknologi 5.0 yang berbasis Al-Qur'an. an dan Al-Hadits. Kata kunci: kompetensi lulusan, pembiasaan, kegiatan keagamaan, keterampilan